The Ideal Concept of Dispute Resolution of Regional Head Election Results in the Constitutional Court - Ratu, Alfian (AIBPM Publisher, 2024)
Direct Regional Head Elections can be understood more closely to the meaning of democracy. Pilkada underwent a change in term to Pemilukada, when Pilkada was categorized as part of the election, because it was followed by the transfer of authority to adjudicate disputes over election results from the Supreme Court (MA) to the Constitutional Court (MK).The purpose of this study is to find the ideal concept of dispute resolution of regional head election results. Elections are general elections to elect regional heads and deputy regional heads. In its development, the problem of the implementation of elections often occurs disputes, especially the results of the implementation of the election itself. In the Regional Head General Election Dispute is very complicated, many factors influence it both in terms of legal material violations and formal violations. Based on the results of the research found, there is a Comparison of the Periodization of Judicial Disputes of Pemilukada. With the above problems, it shows that problems in law enforcement are related to solving problems that are fair and have legal certainty in resolving election disputes. The conclusion in this study is the ideal concept of dispute resolution of future election results related to the scope of authority, legal position of the parties, object of dispute, grace period, content of application, case examination, evidence and decision.